Mitigating dye and organic pollutant-driven surface water pollution using ZnO nanoparticles: a sustainable strategy for climate resilience - Kaur, Navneet; Bansal, Mamta; Kaur, Prabhjot; Kaur, Kirandeep; Awasthi, Amit; Nippani, Satya Krishna; Das, Sumanta; Lodh, Abhishek (Frontiers in Environmental Science, 2025)
Surface water pollution consists of various pollutants like heavy metals (Cu, Cr, Pb, and Ni), metalloids (Se, As, and Ag), and organic pollutants (dyes, antibiotics, pharmaceuticals, pesticides, and phenolic compounds). The escalating issue of water pollution requires innovative solutions for mitigation and climate resilience. Although various advanced techniques are being developed for removing organic pollutants from surface water, nanoparticles (NPs) for the treatment of toxic dyes, antibiotics, and other organic pollutants are not yet efficiently used. In recent years, ZnO NPs have been studied for photocatalytic degradation of dyes and other organic pollutants. In the present review, efforts have been made to understand the role of ZnO NP in the area of treating contaminated surface water due to dyes and organic pollutants, aligning with the United Nations’ Sustainable Development Goals for clean water and sanitation. The review starts with the bibliographical analysis of the last 10 years from 2015 to June 2025, retrieved from the SCOPUS database. Based on the bibliographic analysis, an increasing trend has been noted in scholarly interest and publications related to ZnO NPs in the last decade. The review offers a detailed understanding of the role of ZnO NPs in removing organic pollutants and dyes from surface wastewater. The mechanisms of degradation, adsorption, and photocatalysis are discussed alongside environmental consequences due to the use of ZnO NPs. Additionally, challenges and future directions for enhancing the environmental performance of ZnO-based nanomaterials are explored. In conclusion, ZnO NPs play an important role in surface water purification; however, further research is needed to fully understand their long-term environmental impacts.